SCOTT CARLIN’S GRIEVING PROCESS IN THE KING OF STATEN ISLAND (2020): A KÜBLER-ROSS PSYCHOLOGICAL ANALYSIS - Yoga Pratama; Calvin Dominggo Hattu; Syarif Hidayat; Alia Afiyati (Universitas Islam Negeri Sunan Gunung Djati, 2026)
Previous studies on The King of Staten Island (2020) have largely focused on themes of masculinity, adulthood, or autobiographical elements of the filmmaker, while psychological analyses of grief in the film remain limited and theoretically underexplored. This study addresses this gap by examining Scott Carlin’s grieving process through Elisabeth Kübler-Ross’s Five Stages of Grief, while critically acknowledging contemporary perspectives that conceptualize grief as non-linear and cyclical. Employing qualitative narrative analysis, this research integrates an intrinsic approach, focusing on characterization, plot development, and setting, with an extrinsic psychological framework to interpret Scott’s emotional responses to loss. Data were collected through systematic note-taking, in which selected dialogues, actions, and key scenes were categorized based on explicit emotional indicators corresponding to denial, anger, bargaining, depression, and acceptance. The findings demonstrate that Scott experiences all five stages in a non-linear pattern, with denial and anger recurring most prominently, while acceptance emerges gradually through relational transformation rather than emotional resolution. This study contributes to psychological film analysis by demonstrating how Kübler-Ross’s model can be applied flexibly rather than sequentially, thereby reflecting the complexity of grief representation in contemporary cinema. Practically, the findings highlight the potential of movie scripts as a medium for fostering emotional awareness and understanding of unresolved grief, particularly among young adults.